Rancang Bangun Akuarium Pintar Berbasis Mikrokontroler ESP32 untuk Pengendalian Suhu dan pH Air Secara Real-Time - M. Yusuf Syamsudin (Institute of Information Technology and Social Science (IITSS), 2021)
Maintaining ornamental fish in an aquarium requires stable water quality control, particularly in terms of temperature and acidity (potential of hydrogen or pH). Mismatches between these parameters can cause stress to the fish, weaken their immune systems, and potentially lead to death. This research aims to design and build a smart aquarium system based on an ESP32 microcontroller that is capable of automatically monitoring and controlling water temperature and pH in real time through Internet of Things (IoT) technology. The system uses a waterproof DS18B20 temperature sensor, a 4502C pH sensor, a relay module, a water heater, and pH buffer-up and buffer-down actuators. Measurement data are sent to the cloud and displayed on a web-based interface. The test results showed that the system was able to control water temperature within the range of 26–28 °C and water pH within the range of 6.5–7.2 automatically. All components functioned according to their design specifications, with data transmission delays influenced by internet network stability. Overall, the system is considered effective in supporting more efficient and controlled ornamental fish maintenance.